Amniotic fluid-derived stem cells: potential factories of natural and mimetic strategies for congenital malformations - Cristiane S. R. Fonteles; Julia Enterria-Rosales; Ying Lin; John W. Steele; Ramiro A. Villarreal-Leal; Jing Xiao; Daniel I. Idowu; Beck Burgelin; Bogdan J. Wlodarczyk; Richard H. Finnell; Bruna Corradetti (Stem Cell Research & Therapy)
Abstract Background: Mesenchymal stem cells (MSCs) derived from gestational tissues offer a promising avenue for prenatal intervention in congenital malformations although their application is hampered by concerns related to cellular plasticity and the need for invasive, high-risk surgical procedures. Here, we present naturally occurring exosomes (EXOs) isolated from amniotic fluid-derived MSCs (AF-MSCs) and their mimetic analogs (MIMs) as viable, reproducible, and stable alternatives. These nanovesicles present a minimally invasive therapeutic option, addressing the limitations of MSC-based treatments while retaining therapeutic efficacy. Methods: MIMs were generated from AF-MSCs by combining sequential filtration steps through filter membranes with different porosity and size exclusion chromatography columns. A physicochemical, structural, and molecular comparison was conducted with exosomes (EXOs) released from the same batch of cells. Additionally, their distribution patterns in female mice were evaluated following in vivo administration, along with an assessment of their safety profile throughout gestation in a mouse strain predisposed to neural tube defects (NTDs). The possibility to exploit both formulations as mRNA-therapeutics was explored by evaluating cell uptake in two different cell types(fibroblasts, and macrophages) and mRNA functionality overtime in an in vitro experimental setting as well as in an ex vivo, whole embryo culture using pregnant C57BL6 dams. Results: Molecular and physiochemical characterization showed no differences between EXOs and MIMs, with MIMs determining a threefold greater yield. Biodistribution patterns following intraperitoneal administration were comparable between the two particle types, with the uterus being among targeted organs. No toxic effects were observed in the dams during gestation, nor were there any malformations or significant differences in the number of viable versus dead fetuses detected. MIMs delivered a more intense and prolonged expression of mRNA encoding for green fluorescent protein in macrophages and fibroblasts. An ex-vivo whole embryo culture demonstrated that MIMs mainly accumulate at the level of the yolk sac, while EXOs reach the embryo. Conclusions: The present data confirms the potential application of EXOs and MIMs as suitable tools for prevention and treatment of NTDs and proposes MIMs as prospective vehicles to prevent congenital malformations caused by in utero exposure to drugs.